1997
DOI: 10.1002/(sici)1098-2744(199709)20:1<10::aid-mc3>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Induction of PA2.26, a cell-surface antigen expressed by active fibroblasts, in mouse epidermal keratinocytes during carcinogenesis

Abstract: The monoclonal antibody PA2.26, produced against mouse epidermal keratinocytes transformed with 7,12-dimethylbenz[a]anthracene (DMBA), recognizes a 43- to 47-kDa cell-surface protein that was absent from non-tumorigenic epidermal keratinocytes but present in transformed epidermal cell lines as well as cultured normal fibroblasts. In vivo, the antigen was absent from normal epidermis but induced in basal-like epidermal keratinocytes and dermal fibroblasts during tissue regeneration after wounding and treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
105
1
4

Year Published

2003
2003
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(114 citation statements)
references
References 27 publications
4
105
1
4
Order By: Relevance
“…We also showed that the CT cells are non-smooth muscle and non-blood endothelial cells. Furthermore, podoplanin/PA2.26 has been reported to be upregulated in vivo on murine dermal fibroblast-like cells in activated wounded skin, on cultured fibroblasts (Gandarillas et al 1997) and on a mouse osteoblastic cell line (Nose et al 1990). In the ED specimens, we found podoplanin-expressing CT cells in bone cavities surrounding the VA and juxta-positioned to the margin of the bone matrix.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We also showed that the CT cells are non-smooth muscle and non-blood endothelial cells. Furthermore, podoplanin/PA2.26 has been reported to be upregulated in vivo on murine dermal fibroblast-like cells in activated wounded skin, on cultured fibroblasts (Gandarillas et al 1997) and on a mouse osteoblastic cell line (Nose et al 1990). In the ED specimens, we found podoplanin-expressing CT cells in bone cavities surrounding the VA and juxta-positioned to the margin of the bone matrix.…”
Section: Discussionmentioning
confidence: 99%
“…Podoplanin is a membrane bound glycoprotein shown to be important for the formation of cell surface protrusions and to promote migration and adhesion (Schacht et al 2003;Martin-Villar et al 2005). In dermis podoplanin seems to be induced on interstitial CT cells during inflammation and carcinogenesis (Gandarillas et al 1997). Interestingly, ectopic expression of PA2.26/podoplanin in mouse keratinocytes induces an epithelial-fibroblastoid morphological conversion or trans-differentiation to a phenotype with increased plasma membrane projections and enhanced motility (Scholl et al 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, podoplanin can induce platelet aggregation in vitro . In pathological situations studied thus far, the mouse homologue of podoplanin (PA2.26, OTS-8) is induced in mouse skin during tissue regeneration after wounding and treatment with carcinogenic phorbol 12-myristate 13-acetate (Gandarillas et al, 1997). OTS-8 is also induced by 12-Otetradecanoylphorbol-13-acetate in mouse osteoblastic cells and is constitutively expressed in oncogenic Ras-transformed cells (Nose et al, 1990).…”
Section: Podoplanin Is Expressed In Most Human Tissuesmentioning
confidence: 99%
“…In pathological situations studied thus far, the mouse homolog of podoplanin is induced in mouse skin during tissue regeneration after wounding. 6 The homolog is also constitutively expressed in oncogenic Ras-transformed cells. 7 These Key words: head and neck squamous cell carcinoma (HNSCC), oral cavity, oropharynx, podoplanin, immunohistochemistry, tissue microarray, sentinel node biopsy *S.J.S.…”
mentioning
confidence: 99%